2013
DOI: 10.1021/jf4013778
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antioxidant Peptide Derived from the Ultrafiltrate of Ovomucin Hydrolysate

Abstract: The techno-functional properties of ovomucin as a gel-forming agent and its biological properties are well-known. The aim of the present study was to investigate antioxidant activity in ovomucin hydrolysate using radical scavenging assays. Electrophoresis showed that ovomucin isolated from whole egg was well separated. Ovomucin hydrolysis was carried out using microbial protease according to different incubation times. These ovomucin hydrolysates exhibited 85% antioxidant activity as measured by the 2,2'-azino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 40 publications
5
45
0
Order By: Relevance
“…Previous reports indicated that acidic amino acids played a critical role in hydroxyl radical scavenging activities of peptides, which is related to the carboxyl and amino groups in their side chains (Pan et al, ; Udenigwe & Aluko, ). Similar results were also reported by Chang et al who found that acidic (glutamic acid and aspartic acid) amino acid residues in the sequences of NTDGSTDYGILQINSR and LDEPDPLI were critical for their antioxidant activities (Chang et al, ). Hence, high content of glutamic acid and aspartic acid in HFP may be a favorable factor for its antioxidant activities.…”
Section: Resultssupporting
confidence: 84%
“…Previous reports indicated that acidic amino acids played a critical role in hydroxyl radical scavenging activities of peptides, which is related to the carboxyl and amino groups in their side chains (Pan et al, ; Udenigwe & Aluko, ). Similar results were also reported by Chang et al who found that acidic (glutamic acid and aspartic acid) amino acid residues in the sequences of NTDGSTDYGILQINSR and LDEPDPLI were critical for their antioxidant activities (Chang et al, ). Hence, high content of glutamic acid and aspartic acid in HFP may be a favorable factor for its antioxidant activities.…”
Section: Resultssupporting
confidence: 84%
“…Met residue acted as a reactive site in the PMRGGGGYHY, WMFDW, WMGPY, and EMGPA through formatting a sulfoxide structure to scavenge free radicals [18,56]. Pro residue can help antioxidant peptides, such as LDEPDPL, WMGPY and EMGPA, scavenge ROS because of the pyrrolidine ring [18,57]. Furthermore, aromatic groups of Trp, Phe, and Tyr residues can scavenge free radicals by providing protons [55][56][57][58].…”
Section: Structure-activity Relationship Of Mmp-4 Mmp-7 and Mmp-12mentioning
confidence: 99%
“…A longer incubation period of 15 or 30 min has also been adapted by some authors (Chang et al, 2013;Gómez-Ruiz, López-Expósito, Pihlanto, Ramos, & Recio, 2008). There is a lack of consensus about the optimal incubation time.…”
Section: Introductionmentioning
confidence: 99%